Nonlinear Association Between Red Cell Distribution Width-to-Albumin Ratio and Retinopathy: A Cross-Sectional Study - Gu J; Qiu S; Sun Z (Journal of Multidisciplinary Healthcare)
Jinjin Gu,1,2 Shanhu Qiu,3 Zilin Sun1 1Department of Endocrinology, Zhongda Hospital, Institute of Diabetes, School of Medicine, Southeast University, Nanjing, People’s Republic of China; 2Department of Geriatrics, The Affiliated People’s Hospital of Jiangsu University, Zhenjiang, People’s Republic of China; 3Department of General Practice, Zhongda Hospital, Institute of Diabetes, School of Medicine, Southeast University, Nanjing, People’s Republic of ChinaCorrespondence: Shanhu Qiu, Department of General Practice, Zhongda Hospital, Institute of Diabetes, School of Medicine, Southeast University, No. 87 Dingjiaqiao, Nanjing, 210009, People’s Republic of China, Fax +86-025-83262810, Email tigershanhu@126.com Zilin Sun, Department of Endocrinology, Zhongda Hospital, Institute of Diabetes, School of Medicine, Southeast University, No. 87 Dingjiaqiao, Nanjing, 210009, People’s Republic of China, Email sunzilin1963@126.comPurpose: The red cell distribution width-to-albumin ratio (RAR), a marker of systemic inflammation and nutritional status, has been associated with diabetic retinopathy. However, its relationship with retinopathy in a nationally representative sample of US adults aged 40 and older, including both diabetic and nondiabetic individuals, and the potential nonlinear association remains underexplored.Patients and Methods: This cross-sectional study included 4,753 adults aged 40 and older from the National Health and Nutrition Examination Survey (NHANES) 2005– 2008. Retinopathy was evaluated through fundus photography and classified based on the Early Treatment Diabetic Retinopathy Study (ETDRS) grading protocol. Nonlinear associations between RAR and retinopathy risk were evaluated using generalized additive models, with a two-piecewise linear regression employed to identify the inflection point.Results: The prevalence of retinopathy increased with higher quartiles of RAR (P < 0.001). A nonlinear association was identified, with an inflection point at 3.14. Below this inflection point, each 1-unit increase in RAR was associated with approximately 2.69 times higher odds of retinopathy (OR = 3.69; 95% CI: 1.37– 9.96). Above the inflection point, the association plateaued (OR = 1.14; 95% CI: 0.60– 2.14). Participants in the highest RAR quartile had 56% higher odds of retinopathy compared to those in the lowest quartile (OR = 1.56; 95% CI: 1.16– 2.11).Conclusion: RAR exhibits a nonlinear association with retinopathy and may serve as a risk stratification tool in clinical and public health settings.Keywords: red cell distribution width-to-albumin ratio, retinopathy, nonlinear threshold effects, cross-sectional study